The Evaluasi Dampak Akreditasi Puskesmas Terhadap Kualitas Layanan Dan Pencapaian Uhc Di Indonesia - Aulia Rahma, Fadilah; Wasir, Riswandy; Istanti, Novita Dwi; Apriningsih; Hanifah, Laily (Jurnal Khazanah Intelektual, 2025)
Universal Health Coverage (UHC) is a crucial component of the Sustainable Development Goals aimed at ensuring access to quality healthcare without financial hardship. In Indonesia, the National Health Insurance Program (JKN-KIS) has achieved significant population coverage; however, challenges persist in ensuring healthcare quality, particularly in primary healthcare centers (Puskesmas). This study evaluates the impact of accreditation on improving the quality of primary healthcare services and its contribution to achieving UHC in Indonesia. Drawing from a literature review of 25 articles published between 2015–2024, accreditation has been shown to enhance service quality, particularly in responsiveness and patient satisfaction. Key supporting factors include continuous training, regulatory support, and effective management. However, challenges such as limited infrastructure, uneven distribution of healthcare workers, and administrative barriers remain significant, especially in remote areas. Accreditation plays a vital role in advancing UHC, but its success depends on strengthening infrastructure, improving healthcare worker competencies, and integrating accreditation into daily service practices.